2004
DOI: 10.1016/j.rapm.2003.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia after total-hip arthroplasty: comparison of intravenous patient-controlled analgesia with morphine and single injection of femoral nerve or psoas compartment block. a prospective, randomized, double-blind study

Abstract: PCA is an efficient and safe analgesia technique. FNB and PCB should not be used routinely after total-hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 22 publications
5
101
2
2
Order By: Relevance
“…Most patients of both groups were discharged in the third postoperative day and almost all patients of the sample were discharged before the fourth postoperative day. Our results are different from studies suggesting that cLPB speeds postoperative recovery 8,13 , suggesting that recovery times are similar for both groups. Reports of severe complications and familiarity with other techniques may explain the reluctance of anesthesiologists in choosing LPB.…”
Section: Discussioncontrasting
confidence: 99%
“…Most patients of both groups were discharged in the third postoperative day and almost all patients of the sample were discharged before the fourth postoperative day. Our results are different from studies suggesting that cLPB speeds postoperative recovery 8,13 , suggesting that recovery times are similar for both groups. Reports of severe complications and familiarity with other techniques may explain the reluctance of anesthesiologists in choosing LPB.…”
Section: Discussioncontrasting
confidence: 99%
“…There was no significant difference in the degree of analgesia in the two groups in the first and second postoperative hour, as well as 12 hours after surgery, during rest and during hip flexion. There are a few studies on the effect of single and continuous FNB block as a perioperative analgesia in patients with hip fracture [13,15,16,18,19]. Sirvastativa et al [15] investigated the single FNB block versus psoas compartment block as an analgesia after hip surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar plexus block and blocks of its branches provide excellent analgesia. Blocking plexus lumbalis is performed by rear paravertebral (psoas compartment block) and anterior inguinal paravascular access (n. femoralis block, known as the "3-in-1" block) [13]. An anterior approach provides a simultaneous blockade of n. femoralis, n. cutaneus femoris lateralis and n. Obturatorius; therefore, this technique is called "3-in-1".…”
Section: Doi: 102478/prilozi-2014-0011mentioning
confidence: 99%
“…7,10 However, in 45 patients undergoing total hip replacement, one study compared single shot lumbar plexus and 3-in-1 blocks and failed to detect any difference in nerve block distribution. 13 Two RCTs (combined n = 119) have compared continuous posterior and anterior approaches for patients undergoing total knee replacement. While Morin et al 14 reported similar performance time, onset and success of obturator sensory blockade, Kaloul et al 15 found a better sensory block of the obturator nerve at 24 hr (P = 0.02).…”
Section: Approachesmentioning
confidence: 99%
“…13,14,23 Thus we decided to include the results of these RCTs in the previous section. A review of the literature yielded only one RCT corresponding to our search criteria.…”
Section: Femoral Nerve Blockmentioning
confidence: 99%